An Analysis On Writing Task In English Textbook Entitled English In Focus For The Eight Grade Of Junior High School Students - Sholikhah, Ardiani; , Aryati Prasetyarini, M.Pd; , Dra, Dwi Haryanti. M. Hum (2013)
This research paper aims at analyzing the writing task provided in the textbook entitled English in Focus meet the criteria of writing task suggested by Raimes, and finding whether the writing task in the textbook meet the criteria of writing task suggested by Raimes. In this research, the writer employs descriptive research. The descriptive research is the research to clarify or explain phenomenon. This research uses the content analysis. The method of collecting data is comparing method and analyzing document by selecting the writing tasks on the textbook entitled English in Focus for Junior High School Students that meet the criteria of writing task suggested by Raimes. The results of the research finds of writing tasks provided in the textbook meet the criteria of writing task suggested by Raimes. The criteria of writing task as suggested by Raimes, there are controlled of writing, translation, and free writing. To analyze the writing tasks provided in textbook, the criteria as suggested by Raimes has some components; grammar, mechanics, and word choice. By the percentage the result shows 75% of writing tasks provided in English textbook entitled English in Focus. The writing tasks in textbook entitled English in Focus for Junior High School are categorized good task because the writing tasks in the textbook meet the criteria of writing task as suggested by Raimes.